9(d+2)=3(d-2)

Simple and best practice solution for 9(d+2)=3(d-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(d+2)=3(d-2) equation:


Simplifying
9(d + 2) = 3(d + -2)

Reorder the terms:
9(2 + d) = 3(d + -2)
(2 * 9 + d * 9) = 3(d + -2)
(18 + 9d) = 3(d + -2)

Reorder the terms:
18 + 9d = 3(-2 + d)
18 + 9d = (-2 * 3 + d * 3)
18 + 9d = (-6 + 3d)

Solving
18 + 9d = -6 + 3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3d' to each side of the equation.
18 + 9d + -3d = -6 + 3d + -3d

Combine like terms: 9d + -3d = 6d
18 + 6d = -6 + 3d + -3d

Combine like terms: 3d + -3d = 0
18 + 6d = -6 + 0
18 + 6d = -6

Add '-18' to each side of the equation.
18 + -18 + 6d = -6 + -18

Combine like terms: 18 + -18 = 0
0 + 6d = -6 + -18
6d = -6 + -18

Combine like terms: -6 + -18 = -24
6d = -24

Divide each side by '6'.
d = -4

Simplifying
d = -4

See similar equations:

| -6(-x-7)=90 | | 1128/(-47)= | | 3x+5x=2(4+7) | | -2x-4(0.25+0.5x)=1 | | 15p+7q+5p-4q= | | (1-7i)-(1-5i)= | | 5t-3=7 | | X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) | | 2(9x+5)=-26 | | 3z+1/4=4z+7/4 | | 86=-70+13x | | 2b+4028=51514 | | 17+-5= | | -2(4x+2)=12 | | 5x-x+2=2x+2x+2 | | 2(2x+30)+4x=360 | | (2-4i)+(1-4i)= | | 0=x^2-1 | | 11b-2b= | | 13+(-6n)+(-15)+(-5n)= | | 1.1x+-5.4=-10 | | 5/9x=5/3 | | 1/5x+2/5x+3=18 |

Equations solver categories